Mariawici i Żydzi – rzecz o pomocy - Urszula Grabowska (Zagłada Żydów)
Mariavite Church is a religious movement which split some 100 years ago from the Catholic Church in Poland. Common fate (the persecution and pogroms of the Mariavites at the hands of Roman-Catholics) as well as Mariavites’ tolerance of the other had a marked influence on the development of good relations with the Jews already in the opening years of the 20th c. and even more so during the inter-war period. During the war there were several prominent members of the Mariavitte Church who became involved in saving the Jews, both as members of “Zegota” and on individual basis. One has to list here sister Makryna (Natalia Siuta), bishop M. Franciszek Rostworowski, rev. M. Szczepan Zasadziñski, Mariavite nuns from Felicjanów and others. It seems that the Jews sought Mariavites’ help assuming that the latter would be more inclined to help than the rest of the local population.